Application of Deep Reinforcement Learning for Stock Trading on The Indonesia Stock Exchange - Saepudin, Deni; Rauf, Khalifatur (Prodi Pendidikan Teknik Informatika Universitas Pendidikan Ganesha, 2025)
In the last couple of years, stock trading has gained so much popularity because of its promising returns. However, most investors do not pay attention to the risks of trading without analysis, which can lead to a big loss. Some to reduce these risks, try their luck with automated and pre-programmed trading systems, which are called Expert Advisors. The current study examines the application of DRL for automated assistance in trading with an emphasis on decision-making enhancement, particularly the use of DRL in order to realize high asset returns with a low risk of exposure. Concretely, the two applied DRL methods within this work are A2C and PPO. By systematic testing, the A2C method produced a Sharpe Ratio of 1.6009 with a cumulative return of 1.4468, while the PPO method achieved a Sharpe Ratio of 1.7628 with a cumulative return of 1.4767. These were fine-tuned for the most optimal learning rates, cut loss, and take profit ratios, thus showing great promise with the capability to tune up trading strategies and improve trading performances. The research leverages these DRL techniques, hence arriving at better trading strategies that balance profit and risk, while underlining the promise of advanced algorithms in automated stock trading.